Prevalence of strongyloidiasis in immunocompromised patients in Mazandaran province of northern Iran: A comprehensive study utilizing simultaneous parasitological, serological, and molecular techniques - Reza Saberi; Aliasghar Ghorbanzadeh; Rabeeh Tabaripour; Shahabeddin Sarvi; Shirzad Gholami; Seyed Abdollah Hosseini (Parasite Epidemiology and Control)
Introduction: Strongyloides stercoralis is a soil-transmitted helminth (STH) responsible for strongyloidiasis, a neglected tropical disease (NTD) that affects nearly 614 million people globally. This intestinal nematode poses significant health risks, particularly in immunocompromised individuals. The present study aimed to investigate the prevalence of S. stercoralis in high-risk populations in northern Iran, employing a combination of parasitological, serological, and molecular techniques. Methods: Blood and fecal samples were collected from 92 patients in Mazandaran province, northern Iran, consisting of 52 patients with HIV+/AIDS and 40 cancer patients undergoing chemotherapy or corticosteroid treatment. Initially, all fecal samples were examined using the nutrient agar culture method for parasitological assessment. Following this, DNA extraction was performed on all samples for identify S. stercoralis (by COX1- Nested PCR). Additionally, the sera of the patients were analyzed using the enzyme-linked immunosorbent assay (ELISA) kit (NovaTec Immunodiagnostica GmbH, Dietzenbach, Germany). Results: The stool samples from these patients were negative in agar plate cultures. Among the 92 patients in the study, stool microscopy for Strongyloides rhabditiform larvae was positive in three cases. Using nested PCR, four samples (4.34 %) tested positive for S. stercoralis. Serological investigations revealed that 4 out of 52 HIV-positive patients (7.69 %) and 15 out of 40 cancer patients (37.5 %) had a history of infection with S. stercoralis. Conclusions: These results emphasis the importance of employing a multifaceted diagnostic approach, combining parasitological, serological, and molecular techniques, to accurately identify infections in at risk populations. Given the potential for severe complications associated with strongyloidiasis in immunocompromised individuals, regular screening and prompt treatment are essential to reduce health risks.